Sistem Manajemen Profil Sekolah Dasar Berbasis Web dengan Menggunakan Metode Extreme Programming (Studi Kasus SDN 3 Sindangkasih Purwakarta) - Mutiara Andayani Komara (Jurnal Teknologika, 2025)
The rapid development of information technology has not been fully supported by adequate facilities, resulting in limited dissemination of information to the community. This limitation affects the achievement of student enrollment targets, which have not yet reached an optimal level. This research aims to address the issue by developing a Web-Based Elementary School Profile Management System to introduce SD Negeri 3 Sindangkasih to the wider community. The main problem identified is the lack of effective information media for publishing the school profile, which limits access to information for prospective students and parents. The objective of this study is to design, develop, and implement a web-based information system that comprehensively presents the profile of SD Negeri 3 Sindangkasih. The system is expected to improve information accessibility, expand the school’s promotional reach, and support the process of introducing the school to society. The development method applied is Extreme Programming (XP), an approach that emphasizes collaboration, continuous testing, and adaptability to change. System modeling was carried out using Flowmap and Unified Modeling Language (UML) to visualize workflows and system structures. The system was implemented using PHP, MySQL, XAMPP, and the CodeIgniter (CI) framework. The outcome of this research is an informative and dynamic school profile website. Its main features include a Home Page, Overview, Profile, News & Activities, Achievements, Digital Library, Admission Information, and Contact Us. With this system, the dissemination of information related to SD Negeri 3 Sindangkasih is expected to become more effective and efficient, thereby achieving the goal of introducing the school to a broader audience.